PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Dedy Ghozim Herdiyanto; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the relation between tax avoidance and the firm value. Tax avoidance is convinced as wealth transfer from the government to companies which has obligation to enhance firm value . This study uses annual Cash ETR as a proxy for tax avoidance and Tobin's Q as a proxy for firm value. The sample of this research is non-financial companies listed in Indonesia Stock Exchange for the period 2010 to 2013. Using purposive sampling technique, we find 98 firms with 392 observations. The statistical methods used in this research are Moderated Regression Analysis (MRA) and Path Analysis. The empirical results showed that the tax avoidance effect on firm value. Institutional ownership can not moderate and agency costs can not be an intervening variable in the relation between tax avoidance and firm value.